Tourism's Contribution to an Equal Income Distribution: Perspectives from Local Enterprises. Issue 6 (2nd November 2019) - Nguyen, Van Hoang; Funck, Carolin
ABSTRACT: Although tourism and inequality linkage has received increased attention, limited research considers the perspectives of local businesses in nature conservation areas. This paper explores the perceptions of local enterprises in Yakushima, Japan, concerning tourism's contribution to the local economy, its effects on income distribution, and its impacts on spatial differences among villages. Semi-structured interviews were conducted with 32 local tourism stakeholders. We found that although all respondents perceive tourism as contributing positively to Yakushima's economy, they have different perspectives on income distribution among tourism participants. They also raised questions about the flow of money from tourism. The findings reveal that tourism may not necessarily contribute to equal income distribution and is perceived as creating unequal benefits. Also, it creates a gap between tourist villages and non-tourist villages. Our research suggests that tourism policies aimed at equal income distribution and balanced spatial development should consider the perspectives of all tourism stakeholders.